Risk factors associated with amputations in patients with diabetic foot infection. Seven years of experience in a reference hospital in Panama. The diabetic foot study group at Chiriqui (the FOOTCHI study group) - Pachon Burgos Alvaro; McDonald Posso Anselmo Joaquin; Espinosa De Ycaza Ana; Caballero Arauz Rolando; Quiros Coronel Antonio; Mendoza Elisa (Endocrine and Metabolic Science)
Aims: To determine the risk factors associated with amputations in hospitalized patients with diabetic foot infection. Methods: this is a prospective study conducted at a tertiary care hospital in Panama between January 2010 and December 2016. We included all patients admitted to the hospital with diabetes and diabetic foot infection. A total of 351 patients were included, and a survey to assess for demographic and clinical factors was completed prospectively until discharge. The outcome was lower limb amputation. Results: Sixty-one participants (17.4 %) required a lower limb amputation, and 22 (36.1 %) were major amputations. Several factors were associated with amputation in the univariate analysis: history of foot infection, history of amputation, peripheral arterial disease, a major index ulcer area, duration of the index ulcer >30 days, Grade III 3D severity according to Texas scale, a greater IDSA classification, the presence of necrosis and osteomyelitis. Nevertheless, multiple logistic regression revealed significant relationships between amputations and necrosis (P < 0.0001), osteomyelitis (P < 0.0001), and a severe IDSA classification (P = 0.008). Conclusion: In patients with diabetes foot infection, the presence of osteomyelitis, necrosis and a severe IDSA classification were strongly associated with amputation. Clinical relevance: The rates of lower limb amputations in diabetic foot infections are higher in Hispanics than Caucasians, moreover, data on risk factors for amputation from diabetic foot infection in Latin American countries and specially Central American countries is scarce and there is no data in Panama.